Essential Words for the GRE - Geer, Philip (Barron's Educational Series, Inc., 2016)
An extensive working vocabulary is a prerequisite for test-taking success on the Graduate Record Exam. This book presents 800 graduate-level words with definitions that frequently appear on the exam. Words are used in different contexts to familiarize test takers with their many variations. The book's additional features include a pre-test that helps to diagnose weaknesses, a lengthy word list with extensive practice exercises, and a chapter that discusses and analyzes essential word roots. The book concludes with a post-test to assess progress. Answers are provided for all exercises and for all questions in the pre- and post-test.